2020
DOI: 10.1155/2020/4030826
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA hsa_circ_0000467 Promotes the Development of Gastric Cancer by Competitively Binding to MicroRNA miR-326-3p

Abstract: Circular RNAs are a class of endogenous noncoding RNAs that play an important role in gene regulation. These RNAs are involved in the development and progression of various cancers, but their roles in gastric cancer have not yet been thoroughly elucidated. This study showed that hsa_circ_0000467 expression was higher in gastric cancer tissues than in corresponding adjacent tissues (P<0.050) and that hsa_circ_0000467 expression levels were correlated with gastric cancer histological grade (P<0.050). In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…MiR‐326 was reported to function as a tumor suppressor in multiple cancers such as cervical cancer 29 and non‐small‐cell lung cancer 30 . Additionally, Wang et al showed that hsa_circ_0000467 could sponge miR‐326‐3p and promote gastric cancer development via enhancing cyclin D1 31 . In another study, miR‐326 interacted with circ‐TFF1 in breast cancer progression through regulating TFF1 expression 32 .…”
Section: Resultsmentioning
confidence: 99%
“…MiR‐326 was reported to function as a tumor suppressor in multiple cancers such as cervical cancer 29 and non‐small‐cell lung cancer 30 . Additionally, Wang et al showed that hsa_circ_0000467 could sponge miR‐326‐3p and promote gastric cancer development via enhancing cyclin D1 31 . In another study, miR‐326 interacted with circ‐TFF1 in breast cancer progression through regulating TFF1 expression 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, plasmatic hsa_circ_0089762 may provide discriminative power for the ischemic DCM cohort with high-yield diagnostic accuracy and an AUC of 0.92. These circRNAs have been identi ed mostly in various types of oncologic processes [26][27][28][29][30][31]. Thus, only hsa_circ_0051239 levels have been upregulated in the myocardium of congenital ventricular septal defect [31].…”
Section: Discussionmentioning
confidence: 99%
“…It was identi ed that hsa_circ_0000467 plays a regulatory role in gastric cancer by regulating the level of miRNA-326-3p, and that circRNA may be a potential diagnostic marker and therapeutic target in gastric cancer [40]. It is veri ed that circFUT8 plays an inhibitory role in bladder cancer cells by targeting miRNA-570-3p/KLF10 [41]. In non-human animal research, Zhang et al found that circRNA-006258 regulates the growth and lactation of goat mammary epithelial cells through a circRNA-006258-miR-574-5p-EVI5L regulatory network [42].…”
Section: Discussionmentioning
confidence: 99%